Sphenopalatine ganglion treatment with radiofrequency in a Sluder syndrome young patient - Carmelo Costa; Marilina Schembari (Publiediting, 2014)
Sluder's neuralgia or sphenopalatine ganglion neuralgia is a pain syndrome first described by Sluder in 1908. The clinical picture is characterised by pain starting around the eye and the route of nose. Typically the pain is accompanied by parasympathetic disautonomic signs such as lacrimation and/or rhinorrhea. However, many official headache classifications do not mention the Sluder's neuralgia at all, which is instead classified as a cluster headache (CH). In case of resistance to pharmacological management pain the physician could recur to sphenopalatine ganglion (GSP) neurolytic block with continuous radiofrequency (CRF) or its no ablative alternative with pulsed radiofrequency (PRF). We are presenting a case of a 16-year-old woman who suffered from a typical Sluder's neuralgia successfully treated with GSP PRF.